(untitled) (Research, Society and Development, 2025)
The teaching of literature is extremely important for the development of citizenship in elementary school students, and specifically, the use of poetry linked to differentiated pedagogical tools promotes student development in various aspects, including socialization, critical thinking, and peer bonding. The general objective of this study is to investigate the use of poetry as a teaching resource in the classroom by teachers in the state public school system. The specific objectives are to discuss the problems faced by teachers when working with poetry in basic education and to discuss some possibilities for the use of poetry in teaching in basic education. This article draws on the results of the thesis “The Teaching of Literature, in Particular Poetry, in Public Schools in Gravatá,” by the National University of Rosario. Teachers and students were surveyed about the applicability and perceptions of literature and poetry. It was observed that there is still much to be done to eradicate the teaching of literature and poetry as a tool in basic education, with a shortage of tools and frameworks necessary for teachers to teach this content.